Peningkatan Kualitas SDM Melalui Pelatihan Bahasa Asing Untuk Kampung Biru Arema Malang, Jawa Timur - Juliati, Juliati; Budi, Sri Utami; Goeyardi , Wanda; Widyaningsih, Galih Edy Nur; Rahayuningtyas , Putri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Kampung Biru Arema is one of thematic tourist villages in the city of Malang which provides economic benefits to the residents. The potential development of Kampung Biru is also supported by its strategic location. However, people have difficulty in communicating with foreign tourists due to their limited English speaking competence. Related to this problem, the community service is aimed at improving the quality of human resources by providing foreign language training (English and Chinese). The training was given for two months (June - July 2019). The results showed an improvement in the trainees’ skills and confidence in communicating in English. In addition, the team also have completed writing a booklet that can be used as a reference whenever the residents have difficulties in communication practices with foreign tourists visiting Kampung Biru Arema Malang.